Analisis Implementasi dan Kontribusi Pajak Hotel dan Pajak Restoran Terhadap Penerimaan Pendapatan Asli Daerah di Kabupaten Pulau Morotai - Lukman Wangko (Peneliti.net, 2020)
Based on data from the Ministry of Finance in 2011 in several regions with the lowest PAD in all of Indonesia in Morotai Island Regency. Therefore it is important to increase local taxes. The research objective is to find out more about hotel and restaurant tax approvals and taxes on PAD in Morotai Island Regency and what supports tax management and solutions. This research is a descriptive study using quantitative and qualitative research. The data used are secondary data consisting of PAD from 2011-2014 and primary data in the form of direct interviews. Based on the results of the analysis showing the average criteria are quite good and for the analysis of the average assessment criteria are very effective. Solutions that become challenges and solutions in collection become internal and external solutions as well as internal solutions and external solutions.